ANALISIS TATA NIAGA BIJI KOPI ROBUSTA DI KABUPATEN DAIRI - Yenny Laura Butarbutar; Nurmely Violita Sitorus (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The research background is due to the robusta coffee bean price fluctuation in Dairi District is affect by the oversupply, famine, and selling prices from outside traders. Therefore, a research was conducted to achieve several objectives which are : 1. to identify marketing channel, 2. to analyze total marketing cost, marketing margin and farmer’s share, and 3. to analyze efficiency of the marketing channel robusta coffee bean in Dairi District. The method of determining the area was purposive because Dairi Regency was a production center of robusta coffee bean in North Sumatera Province. The sampling method for farmers used purposive sampling as many as 45 farmers spread in three districts, namely Pegagan Hilir, Sumbul, and Sidikalang subdistricts. The sampling method for middleman used the snowball sampling as many as 22 persons. Based on the research conducted, we can conclude: 1) There are 3 marketing channels in robusta coffee bean in Dairi District; 2) As for total marketing cost, marketing margin and farmer’s share in Dairi District respectively are: Channel I, Rp 2.812,79/kg; Rp 5.775/kg, and 81,07%. Channel II, Rp 2.608,02/kg; Rp 4.453,78/kg, and 90,18%. Channel III, Rp 1.174,79/kg; Rp 0, and 100%. 3) The robusta coffee bean marketing channel in Dairi District for channel I - III are efficient (Ep < 50%).